(untitled) (American Journal of Pedagogical and Educational Research, 2024)
Uzbek folk music is an integral part of the rich cultural heritage of Uzbekistan, a Central Asian nation known for its vibrant traditions and diverse musical expressions. This article delves into the fascinating world of Uzbek folk music, examining its historical development, distinctive characteristics, and cultural significance. By exploring the various genres, instruments, and performance practices, we aim to shed light on the unique cultural tapestry that shapes this traditional musical art form. Through this ethnomusicological journey, we hope to promote a deeper understanding and appreciation of Uzbek folk music, both within Uzbekistan and beyond its borders.